A facile method for fabrication of buckled PDMS silver nanorod arrays as active 3D SERS cages for bacterial sensing1. Issue 62 (11th August 2015) - Kumar, Samir; Lodhi, Devesh K.; Goel, Pratibha; Neeti; Mishra, Prashant; Singh, J. P.
<x xml:space="preserve">Abstract</x> We have successfully demonstrated a simple and facile method to increase the SERS signal of bacteria due to the formation of high density hotspots among the AgNRs and the increase in the area for better interaction of bacteria with the metal surface.